PTH-014 A comparison of patient tolerance of colonoscopy with ct colonography and colon capsule endoscopy. (17th June 2017) - Ojidu, H; Palmer, H; Lewandowski, J; Hampton, J; Blakeborough, T; Epstein, O; McAlindon, ME
Abstract : Introduction: Poor tolerance of laxatives may be associated with inadequate bowel cleansing and reduced pathology detection. [1] Colonoscopy (CS), the gold standard, is uncomfortable, may require sedation and is not without risk. [2] CT colonography (CTC) is less invasive, requires less laxatives, but involves irradiation. Colon capsule endoscopy (CCE) is non-invasive, directly visualises the mucosa, but requires a more vigorous laxative regimen. [3] In this study, patient tolerance of each was compared. Method: Split dose Kleenprep (4L) was used for CS and gastrografin (3 × 30 ml) and rectal insufflation for CTC. The regimen for CCE was either (STH) split dose Kleenprep (4L) plus two phosphosoda 'boosters' or (RFH) split dose Moviprep (2L) with phosphosoda/gastrografin 'boosters'. A bisacodyl suppository was used to promote capsule excretion if needed. Patients graded severity of laxative-related symptoms and recorded a Gloucester Comfort Score (GCS) for each procedure. They scored their overall experience (of bowel preparation and procedure combined) on a visual analogue scale (VAS 0–10: no-intolerable). Results: CS was performed in 153 patients (86M, mn age 58.6±1.2). Prior failed CS, or refusal to have CS, occurred in 30.1% and 18.4%, respectively, of CTC patients (n=103; 36M, mn age 69.5±1.1), and 22.6% and 9.7% of CCE patients (n=31; 8M, mn age 42.9±3.6). CTC and CCE patients were predominantly female (p=0.003 cf. CS cohort, Kruskal Wallis). Moderate to severe laxative-related symptoms prior to CS, CTC and CCE (respectively) were nausea (12.4%, 2.9%, 29.1%; p<0.001), vomiting (2.6%, 3.9%, 8.7%; p=0.004), bloating (11.8%, 1.0%, 16.1%; p<0.001), pain (4.6%, 1.0% and 12.9%; p<0.001), headache (4.6%, 3.9% and 19.4%; p=0.019). GCS scores of moderate to severe discomfort occurred in 40.1%, 7.8% and 0% (p<0.001) and mean VAS scores for the overall experience were 4.9, 2.5 and 3.4 (p<0.001) respectively. Overall CS experience was worse than both CTC (p<0.001, Mann Whitney) and CCE (p=0.01) which yielded similar results. Conclusion: Laxatives may cause distress and the less used, the better. However, procedural discomfort accounts for the overall poorer experience of CS patients compared to CTC and CCE, even though the latter cohorts contain more patients at risk of poorer tolerance (prior failed colonoscopy, refusal of colonoscopy and female predominance.[4] Investigation should be tailored according to the likely diagnoses and patient preference. References: . Holt EW, et al., J Gastrointest Liver Dis 2014;23:135–40. . Standards of practice committee of the ASGE. Gastrointest Endosc 2011;74:745–752. . Spada C, et al., Gut 2015;64:272–281. . Ojidu H, McAlindon ME. Gut2016;65(1):A61. Disclosure of Interest: None Declared